Effect of compost inoculants, temperature and indigenous technical knowledges on decomposition process of rice crop residue - Meena, R.K.; Arya, M.P.S.; Meena, A.L.; Singh, Y.V.; Shukla, Livleen; Meena, H.S. (Annals of Agricultural Research, 2016)
An open pit field experiment was conducted during rabi (dry) season of 2015-16 at Modipuram,India to study the effect of compost inoculants and indigenous technical knowledges (ITKs) ondecomposition of rice residue. The experiment was conducted with nine treatments, rice residue(control); rice residue + cow urine 10% spray; rice residue + 4% urea spray; rice residue + 8% ureaspray; rice residue + compost inoculants (IARI); rice residue + compost inoculant (Trichoderma Sp.);rice residue + molasses 5% spray; rice residue + molasses 5% spray +4% urea spray; rice residue +compost inoculants (IARI) + molasses 5% spray. Forty kg rice straw was stacked in 3 layers of 1 mheight, 1 m width, and 1.5 m length to form a pile. The pile was sprinkled with water at regularintervals. ICAR-IARI compost inoculants is charcoal based solid mix formulation of hyperlignocellulolyticfungi namly Aspergillus nidulans, Trichoderma viride, Phanerochaete chrysosporium andAspergillus awamori. Under ITKs molasses, cow urine and urea solution were applied on rice strawwith in layers. The result of this experiment indicated that the highest value of C/N was recordedwith control (87.2, 81.3 and 78.6) while lowest value recorded with compost inoculants+ molasses5% spray (66.6, 60.7 and 57.0) at 20, 40 and 60 days interval, respectively. Lowest value of C/N ratiowith compost inoculants + molasses 5% spray might be due to higher multiplication of appliedcompost inoculants with 5% molasses.Highest concentration of P and K was recorded with controland lowest value with compost inoculants + 5% Molasses spray. This value might be due to highmicrobial growth in compost inoculant+ 5% molasses spray.